Nanorobots: Magnetically Propelled Fish‐Like Nanoswimmers (Small 44/2016). Issue 44 (November 2016) - Li, Tianlong; Li, Jinxing; Zhang, Hongtao; Chang, Xiaocong; Song, Wenping; Hu, Yanan; Shao, Guangbin; Sandraz, Elodie; Zhang, Guangyu; Li, Longqiu; Wang, Joseph
Abstract : A highly efficient body‐deformable nanoswimmer that emulates the body and caudal fin propulsion of fish swimming is developed by L. Li, J. Wang, and co‐workers on page 6098. The undulatory motion of the nanofish under an oscillating magnetic field allows it to propel in low Reynolds number fluid environments. The new fish‐like deformable nanoswimmer holds considerable promise for practical applications, such as targeted drug delivery and lab‐on‐a‐chip devices.